Bioinformatic identification of lentivirus transfer plasmid contamination causing false-positive HIV NAT results in a high-throughput molecular screening laboratory - Secret, Shannah; Mayne, Richard; Reid, Kaitlin; Hook, Lilian; Lloyd-Evans, Paul; Maddox, Victoria; Miflin, Gail; Brailsford, Su; Sell, Joanne; Golubchik, Tanya; Breuer, Judith; Simmonds, Peter; et al. (American Society for Microbiology, 2026)
Blood screening programs require ultra-sensitive high-throughput PCRs to ensure the absence of pathogens to keep blood components safe for recipients. We present here details of an investigation wherein samples undergoing screening using a high-throughput multi-pathogen NAT assay began to exhibit an abnormally high HIV false reactivity rate. NHS Blood and Transplant usually sees up to 10 HIV reactive samples per year, but this increased to over 100 in just a few days. Investigations into the cause were imperative to prevent recurrence. Analyzer and reagent issues were ruled out and environmental swabbing revealed extensive contamination of the laboratory, with 356 of 392 swabs testing positive. We demonstrate the methods by which we used amplicon NGS and a custom bioinformatic approach to differentiate between expected amplicons, PCR artifact, and contaminant sequences from extracted false-positive samples. Our investigation was able to trace the source of contamination to an unexpected source, a lentivirus transfer plasmid, containing the long terminal repeat (LTR) region of HIV-1, from a neighboring laboratory. This incident demonstrates the risks of false reactivity from HIV-derived lentiviral vectors, which has also been seen in patients receiving lentiviral vectors as part of gene or CAR T-cell therapies. The nature of the contaminant meant that there was no risk to donors, recipients, or staff. It did, however, demonstrate the critical importance of facility design and operation in plasmid manufacturing sites to prevent the spread of such contaminants and avoid unexpected downstream consequences such as those encountered in the screening laboratory.